(untitled) (Journal of Atomic and Molecular Sciences, 2013)
A simple scheme is presented for generating three-atom W state via nonresonant Jaynes-Cummings model. In the proposed protocol, it is injected two two-level atom initially prepared in the excited state and ground state through the cavity prepared in the vacuum state. The third two-level atom is prepared in the ground state and three two-level atom are injected into the second cavity prepared in the vacuum state. The experiment of the proposed scheme is feasible.